DIALOG ILMU DAN IDEOLOGI : PENCARIAN TITIK TEMU ILMU DAN IDEOLOGI - Widisuseno, Iriyanto (HUMANIKA, 2017)
The scientific development nowadays are very quickly. On the other hand, every nation on the world have been protected his ideology. These both have an exsistence characteristics, and on their historical development are always contradiction. The scientific sociological approach as one alternative solution to compromise these contradiction, these both can do the social demand supporting.Science must develop social aspects, and ideology must be open to the possibility of criticism. Pancasila as ideology provides a framework of the value of scientific ethics in the development of science.